Mass transport limited currents at the tubular electrode - Thompson, M; Klymenko, O; Compton, R (2005)
The convective-diffusion equation describing mass transport in a hydrodynamic tubular electrode is given and is solved using the alternating direction implicit method. Models which simplify the full mass transport equation are described and are compared with the approximate Levich theory for flow in a tubular electrode. Limiting currents are compared and the conditions for which the radial and axial diffusion terms are important are determined. © 2004 Elsevier B.V. All rights reserved.